The Leça da Palmeira Waterfront. Wanderings through time and space, toward Siza's "artequitecture" - Abreu, José Guilherme; Mesquita, Mário (Farol, 2025)
This article examines the historical, urban, and architectural evolution of the Leça da Palmeira Waterfront (Portugal), from the 19th century to the present day, with an emphasis on the transformation driven by the Port of Leixões and the seminal intervention of architect Álvaro Siza Vieira. Through a diachronic analysis, the authors explore how the coastal landscape, initially marked by fishing activities and bourgeois summer vacations, was reconfigured by port and industrial infrastructures, culminating in Siza's urban plan (1960–1984). This project, articulated through the concept of "artequitecture," an organic fusion of architecture, landscape, and art, materialized in works such as the Boa Nova Tea House, the Memorial to António Nobre, and the Tidal Pool, which redefined the identity of the place. The text also discusses contemporary challenges, such as the decommissioning of the Sacor Refinery (2021) and the tension between heritage preservation and new occupations, highlighting the fragility of the boundary between natural and humanized spaces.
Keywords: Álvaro Siza Vieira; Architectural heritage; Port of Leixões